2020
DOI: 10.21468/scipostphys.8.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Riemann surfaces for KPZ with periodic boundaries

Abstract: The Riemann surface for polylogarithms of half-integer index, which has the topology of an infinite dimensional hypercube, is studied in relation to onedimensional KPZ universality in finite volume. Known exact results for fluctuations of the KPZ height with periodic boundaries are expressed in terms of meromorphic functions on this Riemann surface, summed over all the sheets of a covering map to an infinite cylinder. Connections to stationary large deviations, particle-hole excitations and KdV solitons are di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 574 publications
(1,195 reference statements)
2
49
0
Order By: Relevance
“…As mentioned before, if we consider the one-point function and step initial condition, Quastel-Remenik's result is Corollary 1.3 for u = U KPZ . 7 In the context of the periodic TASEP, Prolhac [37] noticed that ∂ xx det(I − K z ) is "a reminiscent of soliton solutions for the KP equation". Corollary 1.3 establishes a precise connection.…”
Section: Integrable Differential Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, if we consider the one-point function and step initial condition, Quastel-Remenik's result is Corollary 1.3 for u = U KPZ . 7 In the context of the periodic TASEP, Prolhac [37] noticed that ∂ xx det(I − K z ) is "a reminiscent of soliton solutions for the KP equation". Corollary 1.3 establishes a precise connection.…”
Section: Integrable Differential Equationsmentioning
confidence: 99%
“…To evaluate this integral asymptotically using the method of steepest-descent, it turned out that we need to consider an analytic continuation of polylog functions on a Riemann surface and the main contribution comes from a boundary point on a new sheet of the Riemann surface. Recently motivated by the same function F (x; τ, γ), Prolhac [37] studied Riemann surfaces associated to general polylog functions. In this paper, we carry out the analytic continuation directly for polylog functions of positive half integer index.…”
Section: Large Time Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was shown that the height CDF at the (large time) KPZ fixed point for the full space problem is related to scale-invariant solutions of the Kadomtsev-Petviashvili (KP) equation [121]. A related observation was made for the periodic KPZ fixed point [122]. This connection to the KP equation extends to the generating function at arbitrary time for the KPZ equation in full space, for some particular initial conditions, droplet, half-Brownian [121] and Brownian [123].…”
Section: E Extended Kernel and The Kadomtsev-petviashvili Equationmentioning
confidence: 99%
“…[92], by representing the polylogarithm as a sum of Hurwitz zeta functions (equation (57) in Ref. [92]), or as an infinite sum of square roots (equation (62) in Ref. [92]) with well-defined cuts.…”
Section: Large-activity Fluctuations Of the Edwards-wilkinson Regimementioning
confidence: 99%